Early detection of periodontitis among young adult cigarette smokers and non-smokers using cone beam computed tomography - Kadhem, Maisam A; Ali, Basima G; Al-Naimi, Shifa H (Journal of Baghdad College of Dentistry, 2014)
Background: Periodontitis is an inflammatory disease that affects the supporting tissues of the teeth; Smoking is an important risk factor for periodontitis induces alveolar bone loss and cause an imbalance between bone resorption and bone deposition. The purpose of this study is to detect and compare the presence of incipient periodontitis among young smokers and non-smokers by measuring the distance between cement-enamel junction and alveolar crest (CEJ-Ac) using Cone Beam Computed Tomography (CBCT). Material and methods: The total sample composed of fifty two participants, thirty one smokers and twenty one non-smokers (age range 14-22 years). Periodontal parameters: plaque index (PLI), gingival index (GI) were recorded for all teeth except the third molar while the radiographic analysis using CBCT was recorded on the Ramfjord teeth, the unit of measurement was from cement-enamel junction to alveolar crest distance (CEJ-Ac distance) per site in millimeters. Results: The results obtained were a non significant difference for PLI, a significant difference of mean of GI between young smokers and non smokers. There was a highly significant difference in the general mean of CEJ-Ac distance between both groups. There was a significant difference between maxillary and mandibular teeth, a non significant difference between right and left sides among young smokers and non smokers. Conclusion: The CBCT device plays an important role in detection the incipient form of periodontitis among young smokers and non-smokers, so we concluded that there is a highly significant difference in the general mean CEJ-Ac distance between young smokers and non smokers with increase distance in the maxillary teeth than that in the mandibular teeth.